A Challenging and Rare Case of Metastatic Follicular Dendritic Cell Sarcoma Originating from a Tonsil. (28th October 2021) - Gallardo, J; Watson, E; Finch, C J; Xu, Y
Abstract: Introduction/Objective: Follicular dendritic cell sarcoma (FDCS) is a rare malignant tumor of follicular dendritic cells. Most cases of FDCS are described in lymph nodes, but it can involve extra-nodal locations such as the tonsil. Methods/Case Report: We report a case of a 55-year-old male with a 6-month history of a slow growing left neck mass. The patient had a poorly differentiated carcinoma of the left tonsil diagnosed based on morphologic features eight years ago, followed by chemoradiation, and subsequent left tonsillectomy without tumor identified. Imaging reported a 4.0 cm mass in the left neck level III lymph node location. Biopsy of the mass revealed a spindle cell neoplasm. It was difficult to reach a definitive diagnosis despite an extensive work-up. Review of the previous left tonsil biopsy showed a pleomorphic epithelioid cell proliferation. On the radical resection specimen of the left neck mass, a 4.5 cm, tan-gray, fleshy, necrotic mass was present. Microscopically, it demonstrated a neoplasm with spindle cell and epithelioid cell proliferation, with extensive necrosis. A wide panel of immunostains was performed; the tumor cells showed positivity for CD21, CD23, CD35, and focally weak positivity for cytokeratin OSCAR and Synaptophysin. Squamous cell markers were negative. These findings are consistent with FDCS. Further work-up on the original tonsil tumor displayed immunostaining profile of FDCS. This case was consulted with the National Institute of Health (NIH) for confirmation of the diagnosis. Results (if a Case Study enter NA): NA Conclusion: Morphologically, FDCS can present with various histologic patterns, which can lead to diagnostic pitfalls, and common confusion with poorly differentiated carcinoma or soft tissue tumors, especially in needle biopsies. Generally, patients present with a prolonged clinical course, with a 50% and 25% chance of recurrence and metastasis respectively, hence the awareness and accurate diagnosis of this entity is important in biopsies of lymph nodes or of extranodal locations such as a tonsil.